2015
DOI: 10.3389/fncel.2015.00445
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Ethanol Regulates Hippocampal GABA(A) Receptor Delta Subunit Gene Expression

Abstract: Chronic ethanol consumption causes structural and functional reorganization in the hippocampus and induces alterations in the gene expression of gamma-aminobutyric acid type A receptors (GABAARs). Distinct forced intermittent exposure models have been used previously to investigate changes in GABAAR expression, with contrasting results. Here, we used repeated cycles of a Chronic Intermittent Ethanol paradigm to examine the relationship between voluntary, dependence-associated ethanol consumption, and GABAAR ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
0
11
1
Order By: Relevance
“…Collectively, this work demonstrates the importance of δ subunit-containing GABA A receptors in the VTA of female mice during binge-like drinking. Further, the evidence of a role for δ subunit-containing GABA A receptors in alcohol consumption also has implications regarding withdrawal, in which changes in δ expression have been observed in the hippocampus 46 ; however, it remains to be determined whether alcohol exposure alters GABA A R δ subunit expression in brain regions implicated in alcohol intake, such as the VTA.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, this work demonstrates the importance of δ subunit-containing GABA A receptors in the VTA of female mice during binge-like drinking. Further, the evidence of a role for δ subunit-containing GABA A receptors in alcohol consumption also has implications regarding withdrawal, in which changes in δ expression have been observed in the hippocampus 46 ; however, it remains to be determined whether alcohol exposure alters GABA A R δ subunit expression in brain regions implicated in alcohol intake, such as the VTA.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen weeks old mice were placed in a dedicated room with 12:12 inverted light/dark cycle and allowed to adapt to the new light/dark cycle for 1 week before the beginning of testing. We used a modified sucrose-fading procedure as we have previously described ( Sanna et al, 2011 ; Follesa et al, 2015 ). Briefly, the mice were provided with daily access to an alcohol solution for 2 h, beginning 30 min prior to the dark cycle start point.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after decapitation, blood samples (140 μl) were collected from the trunk with two heparinized capillary tubes, transferred to 1.5-ml test tubes containing 10 μl heparin, and mixed; 100 μl aliquots of blood was then subjected to BAC analysis by static headspace capillary gas chromatography/mass spectrometry following the same protocol that we previously described in Follesa et al (2015) . BAC values were expressed in mg/dl units.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol exposure can change the expression of GABAAR subunits (Liang et al, 2004;Olsen et al, 2012;Lindemeyer et al, 2014;Follesa et al, 2015) and sex differences in GABAAR δ subunit expression has been reported (Maguire et al, 2005). Given that changes in the expression of the GABAAR δ subunit, whether through genetic deletions or associated with hormone fluctuations during pregnancy, can alter oscillation frequencies in the hippocampus Mody, 2013, 2015), we hypothesized that altered expression of the GABAAR δ subunit, expressed on PV interneurons in the BLA, may contribute to our observed sex differences in BLA network states.…”
Section: Repeated Alcohol Exposure Alters δ Expression On Pv Interneurons In the Blamentioning
confidence: 99%